1998
DOI: 10.1007/s002849900278
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation Patterns of 2,4,6-Trinitrotoluene by Aerobic Bacteria

Abstract: 2,4,6-Trinitrotoluene (TNT), a toxic nitroaromatic explosive, accumulates in the environment, making necessary the remediation of contaminated areas and unused materials. Although bioremediation has been utilized to detoxify TNT, the metabolic processes involved in the metabolism of TNT have proven to be complex. The three aerobic bacterial strains reported here (Pseudomonas aeruginosa, Bacillus sp. , and Staphylococcus sp.) differ in their ability to biotransform TNT and in their growth characteristics in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 30 publications
1
68
2
1
Order By: Relevance
“…In aerobic systems, partially reduced products accumulate. The predominant products under aerobic conditions are the aminodinitrotoluene (ADNT) isomers and, to a lesser extent, 2,4-diamino-6-nitrotoluene and azoxytetranitrotoluenes (4,5,12,17,24,39). A productive reduction of TNT is catalyzed by the nitrate ester reductase from Enterobacter cloacae PB2.…”
mentioning
confidence: 99%
“…In aerobic systems, partially reduced products accumulate. The predominant products under aerobic conditions are the aminodinitrotoluene (ADNT) isomers and, to a lesser extent, 2,4-diamino-6-nitrotoluene and azoxytetranitrotoluenes (4,5,12,17,24,39). A productive reduction of TNT is catalyzed by the nitrate ester reductase from Enterobacter cloacae PB2.…”
mentioning
confidence: 99%
“…Recently, Kalafut et al (121) reported a promising aerobic route for TNT metabolism which led to the production of 2-amino-4-nitrotoluene. This metabolite results from the loss of one of the original nitro groups, leaving two adjacent unsubstituted carbon atoms that can serve as a substrate for oxygenases.…”
Section: Aerobic Metabolism Of Tnt By Bacteriamentioning
confidence: 99%
“…Several researchers have reported TNT degradation by aerobic bacteria, which use denitration pathway [2,4,20,21] and showed that TNT denitration is profitable to bacteria. [22,23] The level of denitration was substantially higher in static cultures than in orbital shaken cultures (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Under many typical setting the rates of degradation are limited, mainly due to the accumulation of intermediate metabolites, and their toxic effects on biological systems. [2] The investigators from various places have isolated several organisms, which degrade explosive aerobically. Most notable among them are Stenotrophomonas, [7] Rhodococcus, [8,9] Enterobacter, [5] Pseudomonas, [10] Mycobacterium, [11] Bacillus, [2] Serratia [12] and Staphylococcus, [2] Halasz et al [13] have reported detection of degradation of explosives by soil indigenous organisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation